2014
DOI: 10.1002/jor.22624
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrophage phenotype and induction of epithelial‐to‐mesenchymal transition genes following acute Achilles tenotomy and repair

Abstract: Tendon injuries occur frequently in physically active individuals, but the clinical outcomes for these injuries can be poor. In many injured tissues the repair process is orchestrated by two types of cells, macrophages and fibroblasts. Macrophages, which have both proinflammatory (M1) and antiinflammatory (M2) phenotypes, can directly participate in tissue remodeling and direct the response of other cells through the secretion of cytokines and growth factors. In many organ systems, epithelial cells can transdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 48 publications
8
135
1
Order By: Relevance
“…Several studies have demonstrated increased expression of inflammatory cytokines including tumour necrosis factor (TNF) α, interleukin-1β (IL-1β) and IL-6 in tendinopathy 1 7 25–27. Tendon healing has been shown to involve changes in inflammatory cytokine expression and changes in macrophage phenotype 28 29. Tenocytes have also been shown to possess TNFα and IL-21 signalling systems,30 31 notably, with IL-21 production being demonstrated to increase in response to the application of TNFα and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated increased expression of inflammatory cytokines including tumour necrosis factor (TNF) α, interleukin-1β (IL-1β) and IL-6 in tendinopathy 1 7 25–27. Tendon healing has been shown to involve changes in inflammatory cytokine expression and changes in macrophage phenotype 28 29. Tenocytes have also been shown to possess TNFα and IL-21 signalling systems,30 31 notably, with IL-21 production being demonstrated to increase in response to the application of TNFα and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…46 Macrophage depletion has been shown to increase the ultimate tensile strength of healing mice Achilles tendons 47. Changes in macrophage phenotype and epithelial-to-mesenchymal transition genes have been noted following Achilles tenotomy and during repair 29. The development of a better understanding of the role of specific cell subpopulations in pathogenesis of tendinopathy and during tendon healing is vital to identify potential therapeutic targets and develop more effective future treatments for patients.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of biological processes of tendon repair and degeneration is required for establishing strategies that stimulate tendon repair and induce its regeneration. Previous studies have profiled expression of inflammatory cytokines in canine and rat tendon injury models [3, 4], and found that gene expression of inflammatory cytokines including IL-1β is remarkably up-regulated. In vitro studies have shown that IL-1β makes tendon fibroblasts decrease the mRNA level of collagen 1 [5], suggesting that IL-1β disturbs function of tendon fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how inflammatory cytokines affect the regenerative and degenerative potential of inTPCs, we focused on IL-1β, one of dominant cytokines that are up-regulated in injured tendons [3, 4] and examined the effects of IL-1β on function of inTPCs. IL-1β strongly inhibited tenogenic, chondrogenic and osteogenic differentiation in inTPCs and altered glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Tendon injuries in MRL mice have an improved healing response with increased mechanical properties and cell proliferation, and a reduction in the macrophage response [124]. Distinct macrophage populations have been shown to infiltrate mammalian tendon tissue at specific stages after injury along with differential regulation of pro-inflammatory cytokines [127]. In addition, much work has been done examining the role of cytokines in tendon cell behaviors [128].…”
Section: Regenerative Model Systemsmentioning
confidence: 99%